Contributions of tenderness, juiciness and flavor liking to overall liking of beef in Europe. (October 2020) - Liu, Jingjing; Ellies-Oury, Marie-Pierre; Chriki, Sghaier; Legrand, Isabelle; Pogorzelski, Grzegorz; Wierzbicki, Jerzy; Farmer, Linda; Troy, Declan; Polkinghorne, Rod; Hocquette, Jean-François
Abstract: This study evaluated the contributions of sensory traits to overall liking in Europe. Perceptions by untrained consumers of tenderness, juiciness, flavor liking and overall liking were determined using the Meat Standards Australia protocols. According to European consumer testing with European beef samples, flavor liking was the most important contributor (39%) to beef overall liking, followed by tenderness (31%) and juiciness (24%) ( P  < .05; R 2  > 0.94). The improvement in tenderness over the last decades may explain the highest contribution of flavor liking nowadays. Flavor liking is therefore the main driver of variability in overall liking. Juiciness is the least robust trait which could be influenced by other traits during consumer perception. For outstanding steaks, each sensory trait should have excellent scores and high contributions to overall liking. For medium cuts, one sensory trait with a low score has the potential to be compensated by other traits with higher scores and more emphasis will be placed on the trait with the lowest perception. Highlights: Flavor liking is the main driver of variability in overall liking. The improvement of tenderness is one of the reasons of increasing contribution of flavor liking to overall liking. Juiciness is the least robust trait that has the least effect size on overall liking. One sensory trait with a low score has the potential to be compensated by other traits with higher scores. More emphasis will be placed on the trait with the lowest perception during the determination of overall liking.